Alemtuzumab long-term immunologic effect: Treg suppressor function increases up to 24 months. Issue 1 (February 2016) - De Mercanti, Stefania; Rolla, Simona; Cucci, Angele; Bardina, Valentina; Cocco, Eleonora; Vladic, Anton; Soldo-Butkovic, Silva; Habek, Mario; Adamec, Ivan; Horakova, Dana; Annovazzi, Pietro; Novelli, Francesco; et al.
Abstract : Objective: To analyze changes in T-helper (Th) subsets, T-regulatory (Treg) cell percentages and function, and mRNA levels of immunologically relevant molecules during a 24-month follow-up after alemtuzumab treatment in patients with relapsing-remitting multiple sclerosis (RRMS). Methods: Multicenter follow-up of 29 alemtuzumab-treated patients with RRMS in the Comparison of Alemtuzumab and Rebif Efficacy in Multiple Sclerosis (CARE-MS) I and CARE-MS II trials. Peripheral blood (PB) samples were obtained at months 0, 6, 12, 18, and 24. We evaluated (1) mRNA levels of 26 immunologic molecules (cytokines, chemokines, chemokine receptors, and transcriptional factors); (2) Th1, Th17, and Treg cell percentages; and (3) myelin basic protein (MBP)–specific Treg suppressor activity. Results: We observed 12 relapses in 9 patients. mRNA levels of the anti-inflammatory cytokines interleukin (IL)–10, IL-27, and transforming growth factor–β persistently increased whereas those of proinflammatory molecules related to the Th1 or Th17 subsets persistently decreased after alemtuzumab administration throughout the follow-up period. PB CD4+ cell percentage remained significantly lower than baseline while that of Th1 and Th17 cells did not significantly change. A significant increase in Treg cell percentage was observed at month 24 and was accompanied by an increase in Treg cell suppressive activity against MBP-specific Th1 and Th17 cells. Conclusions: The long-lasting therapeutic benefit of alemtuzumab in RRMS may involve a shift in the cytokine balance towards inhibition of inflammation associated with a reconstitution of the PB CD4+ T-cell subsets that includes expansion of Treg cells with increased suppressive function.